In vitro activity of zinc oxide-eugenol and glass ionomer cements on Candida albicans - Cassanho, Anna Carolina Aguiar; Fernandes, Aletéia Massula; Oliveira, Luciane Dias de; Carvalho, Claudio Antonio Talge; Jorge, Antonio Olavo Cardoso [UNESP]; Koga-Ito, Cristiane Yumi (FapUNIFESP (SciELO), 2005)
The aim of this study was to evaluate in vitro the antimicrobial activity of glass ionomer (GIC) and zinc oxide-eugenol (ZOE) cements against Candida albicans. Standardized GIC and ZOE specimens were maintained in contact with C. albicans suspension (1 x 10(6) cells/ml) at 37 degrees C for 24 h, 48 h or 7 days. A control group without any testing cement was included. After the incubation period, aliquots of 0.1 ml were plated on Sabouraud's agar, and then the number of colonies was counted. The results were expressed as values of logarithms of colony-forming units per milliliter (log CFU/mL) and were analyzed statistically by Kruskal-Wallis ANOVA. After 48 h of incubation, the ZOE group presented no growth of C. albicans. GIC and control groups presented similar mean values at all tested periods. According to the results obtained, it could be concluded that, under the experimental conditions, ZOE cement was more effective in vitro against C. albicans than GIC.
Keywords: antifungal agent; glass ionomer; topical antiinfective agent; zinc oxide eugenol; analysis of variance; Candida albicans; drug effect; microbiological examination; microbiology; nonparametric test; thrush; tooth pulp; Analysis of Variance; Anti-Infective Agents, Local; Antifungal Agents; Candidiasis, Oral; Dental Pulp Cavity; Glass Ionomer Cements; Microbial Sensitivity Tests; Statistics, Nonparametric; Zinc Oxide-Eugenol Cement